Blendas de carvão vegetal e carvão mineral para a produção de briquetes - Barros, João Lúcio de (Universidade Federal de São Carlos, 2014)
Brazil produces about 37 million cubic meters of charcoal per year whit an increasing due to the gradual coal replacement, once the coal mined in Brazil does not have adequate levels of carbon for some purposes, such as power generation. However, the large amount of coal found in all terrestrial crust propitiates an extremely low cost this product. Regarding to it, whit the intent to add value to the coal and provide an adequate destination to by-product (fine) of the charcoal, it was made briquettes of coal blends. For briquettes production it was used coal and charcoal fines, corn starch and boiling water at different proportions, summing up 25 treatments. Ten samples were made for each treatment, summing 250 specimens, wich were analyzed by the moisture content, proximate analysis, density, mechanical strength and thermal analysis. The treatments without the addition of binder were discarded because briquettes could not be formed from them. Other treatments had good features, reaching satisfactory results expect in relation to the formation briquettes (average mechanical strength of 0,2 MPa), presenting good mechanical strength for commercial application. According to the increased proportion of charcoal in the blend, the produced briquette achieved better results, mainly to thermal properties due to higher fixed carbon content (compared to coal) and reduced ash content, an appropriate behavior for various industrial and even residential applications. It was concluded that the use of by-products from vegetable and coal briquettes was technically feasible, providing advantageous physical characteristics for storage and transportation.
Characterization of blend and briquetes of charcoal and coals
Keywords: Biomassa; Bioenergia; Briquete; Briquetting press; Coal; Waste; Carvão vegetal; Charcoal; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA